Delocalized versus localized excitations in the photoisomerization of azobenzene-functionalized alkanethiolate SAMs. (9th November 2017) - Bronsch, Wibke; Moldt, Thomas; Boie, Larissa; Gahl, Cornelius; Weinelt, Martin
Abstract: Self-assembled monolayers of azobenzene-functionalized alkanethiolates form molecular ensembles with preferential orientation and significant excitonic coupling among the azobenzene chromophores. We have studied their optical switching with differential reflectance and two-photon-photoemission spectroscopy tuning the excitation wavelength through the excitonically broadened S2 absorption band. While the effective isomerization cross-section increases towards shorter wavelengths, the fraction of cis molecules in the photostationary state decreases. We attribute this observation to the absorption of the cis isomer in the SAM. The photoisomerization in the SAM thereby follows the behavior of non-interacting chromophores in solution, despite the formation of H-aggregates. Our study thus reveals that photoswitching occurs via localized excitations while strongly excitonically coupled, delocalized states do not contribute significantly.